Social Connectedness, Excessive Screen Time During COVID-19 and Mental Health: A Review of Current Evidence - Pandya, Apurvakumar; Lodha, Pragya (Frontiers in Human Dynamics, 2021)
With an advancement of digital technology, excessive screen time has become a grave concern. This has pushed researchers and practitioners to focus on digital well-being. Screen time during COVID-19 has further increased as a result of public health measures enforced by governments to curb the pandemic. With the global societies under lockdown, the only medium to stay socio- emotionally connected was the digital one. A lack of comprehensive empirical overviews on screen time in COVID-19 era in the present literature prompted us to conduct this review. The present review attempts to understand the virtual social connectedness, excessive use of digital technology, its consequences and suggest strategies to maintain healthy use of digital technology. Results reveal that screen time has increased drastically during COVID-19. Though there are mixed consequences of prolonged screen time use and blurred understanding between healthy and unhealthy social connectedness over digital media, the suggestions for negative implications on (physical and) mental health warrant a strict need for inculcating healthy digital habits, especially knowing that digital technology is here to stay and grow with time.